It's all about Connections: Evidence on Network Formation - Armin Falk; Michael Kosfeld (Institute for the Study of Labor (IZA), 2003)
We present an economic experiment on network formation, in which subjects can decide to form links to one another. Direct links are costly but being connected is valuable. The gametheoretic basis for our experiment is the model of Bala and Goyal (2000). They distinguish between two scenarios regarding the flow of benefits through a network, the so-called 1-way and 2-way flow model. Our main results show that the prediction based on Nash and strict Nash equilibrium works well in the 1-way flow model but fails largely in the 2-way flow model. We observe a strong learning dynamic in the 1-way flow model but less so in the 2-way flow model. Finally, costs of a direct link have a positive impact on the occurrence of (strict) Nash networks in the 1-way flow model but a negative impact in the 2-way flow model. In our discussion on possible explanations for these results we focus on strategic asymmetry and asymmetry with respect to payoffs. We find that the latter asymmetry, i.e., payoff inequity, plays an important role in the network formation process.
Keywords: Z13; D63; C92; C72; 330; network formation; experiments; coordination; fairness; Soziales Netzwerk; Nichtkooperatives Spiel; Lernprozeß; Nash-Gleichgewicht; Experiment; Theorie